Operationalising user behaviour: a study on the life cycle assessment of smart home technologies - Mareike Tippe; Henning Wigger; Urte Brand-Daniels; Thomas Vogt (Energy, Sustainability and Society)
Abstract Background Smart home technologies (SHT) make it easier than ever to track energy demands and are expected to contribute to the implementation of sustainability strategies. In particular, they are supposed to enable promising demand side management strategies by altering user behaviour towards sustainability while ensuring the balance of energy supply and demand. For determining environmental impacts of products and technologies, the methodology of life cycle assessment (LCA) is an established tool. While large parts of LCAs are standardised, the consideration of user behaviour related effects has not been specified. By adopting an interdisciplinary perspective, this literature study contributes to the future development of a standardized methodology for the operationalisation of behaviour in LCAs. Results Three main strategies for operationalising behaviour in LCA studies were identified: (1) behaviour theory-based approaches, (2) model-based behaviour predictions and (literature-based) deductions, and (3) averages and assumptions. The results of this literature study show that the selection of the strategy is crucial as the user behaviour and methods used for LCAs have a significant impact on the environmental and economic payback periods and calculated overall impact of SHTs. Findings from the social sciences on practices and household activities that can be influenced by SHTs, are not systematically applied. Conclusions Our literature analysis makes it clear that LCA results depend on various factors. Selected operationalisation and methodological approaches, respectively, can play a key role. Depending on the method chosen the results can vary by several orders of magnitude and are not always comparable. Simplified approaches for integrating user behaviour into LCAs like assumptions and average values can be a first step in accounting for the relevance of behaviour. However, it is important to bear in mind that these approaches may not reflect actual user behaviour, as this can be subjected to a limited changeability of certain household practices and habits. On the basis of the results, the authors recommend greater interdisciplinary co-operation in the conduction of LCAs on SHTs, ranging from a common definition of the scope, to the implementation of socio-scientific research and survey methods, to the derivation of policies.